Design and assembly of double-crossover linear arrays of micrometre length using rolling circle replication - Lubrich, D; Bath, J; Turberfield, A (IOP Science, 2005)
We demonstrate the use of rolling circle replication to template linear DNA arrays whose sizes bridge the gap between nanometre-scale self-assembly and top-down lithographic fabrication. Using rolling circle replication we have produced an oligonucleotide containing several hundred repeats of a short sequence motif. On this template we have constructed, by self-assembly, an array consisting of two parallel duplexes periodically linked by antiparallel Holliday junctions. We have observed arrays up to 10 νm in length by atomic force microscopy. © 2005 IOP Publishing Ltd.